Selective laser melting of titanium alloy with 50 wt% tantalum : effect of laser process parameters on part quality - Sing, Swee Leong (2018)
Selective laser melting (SLM) is a powder bed fusion additive manufacturing (AM) technique that produces three-dimensional (3D) parts by fusing metallic powders with a high-energy laser. SLM involves numerous process parameters that may influence the properties of the final parts. Hence, establishing the effect of the SLM processing parameters is important for producing parts of high quality. In this study, titanium-tantalum alloy was fabricated by SLM using a customized powder blend to achieve in situ alloying. The influence of processing parameters on the microstructure and properties such as relative density, microhardness and surface roughness was investigated. The results show that fully dense titanium-tantalum parts can be obtained from SLM. With laser power of 360 W, scan speed of 400 mm/s, powder layer thickness of 0.05 mm and hatch spacing of 0.125 mm, the titanium-tantalum alloy produced by SLM has relative density of 99.85 ± 0.18%. Despite the variation in process parameters, titanium-tantalum shows laminar β grains in random directions in both xy and yz-plane from optical microscope (OM) analysis in all the parts produced. This observation is further confirmed using x-ray diffraction (XRD).